Challenges in molecular diagnosis of multiple endocrine neoplasia - Romanet, Pauline; Charnay, Théo; Sahakian, Nicolas; Cuny, Thomas; Castinetti, Frédéric; Barlier, Anne (Frontiers in Endocrinology, 2024)
Multiple endocrine neoplasia (MEN) is a group of rare genetic diseases characterized by the occurrence of multiple tumors of the endocrine system in the same patient. The first MEN described was MEN1, followed by MEN2A, and MEN2B. The identification of the genes responsible for these syndromes led to the introduction of family genetic screening programs. More than twenty years later, not all cases of MENs have been resolved from a genetic point of view, and new clinicogenetic entities have been described. In this review, we will discuss the strategies and difficulties of genetic screening for classic and newly described MENs in a clinical setting, from limitations in sequencing, to problems in classifying variants, to the identification of new candidate genes. In the era of genomic medicine, characterization of new candidate genes and their specific tumor risk is essential for inclusion of patients in personalized medicine programs as well as to permit accurate genetic counseling to be proposed for families.